Effects of Active Mobility Act and Parking Places (Amendment) Bill on active mobility device parking characteristics - Kang, Kee Hong (2019)
This project investigates the effects of the policy of Parking Places (Amendment) Bill on active mobility device parking characteristics at authorised and illegal parking areas in vicinity of Boon Lay Mass Rapid Transit (MRT) station. Under the geo-fencing technology, shared-bike users would be subject to park shared-bikes only within authorised areas in time to come, potentially causing the increase in parking demand within bike parking areas, thereby leading to parking demand exceeding the design parking capacity of bike parking areas.